Intravitreal Bevacizumab: Safety of multiple doses preparation from single vial in minor theater in tertiary care center - Asghar, Asfandyar; Rizwan, Amna; Obaid, Naila; Sughra, Ume; Naeem, Badar ud Din Ather; Nazir, Tehmina (Pakistan Journal of Ophthalmology, 2020)
PURPOSE: To determine the safety of multiple doses preparation of bevacizumab from single vial in minor theatre in reducing the frequency of endophthalmitis. STUDY DESIGN: Retrospective exposure study PLACE AND DURATION OF STUDY: Department of Ophthalmology, Fauji Foundation Hospital (FFH), Rawalpindi from June 2016 to March 2018. MATERIAL AND METHODS: 1690 eyes belonging to 1001 patients was included using computer logs of patients receiving intravitreal bevacizumab (IVB). In FFH, we allocate three consecutive days every month in order to administer IVB. Approximately 50 patients were typically given IVB over three-days period.1-2 ml (depending upon the number of patients) of bevacizumab was withdrawn in a 3 cc syringe.1 cc insulin syringe with 29 G needle was taken and, 0.05 ml (1.25 mg) bevacizumab was injected from behind using the 3 cc syringe, resulting in preparation of 10-20 injections of IVB. The bevacizumab vial was then stored at 4 degrees Celsius. RESULTS: Total 1690 eyes belonging to 1001 patients were analyzed. The occurrence of endophthalmitis was 2/1690 (0.12%) corresponding to a 95% CI of 0.03%-0.43%, which does not represent an increase in cases as compared to endophthalmitis resulting from using a compounding pharmacy. CONCLUSION: Whereas, a priori, it seems reasonable to assume that aliquot preparation and storage of bevacizumab for intravitreal use particularly by a compounding pharmacy is safer. We, however, show that our preparation of IVB from single vial technique using proper sterilization is equally safe. Due to the reduced cost of our technique, we recommend it, particularly in the developing world.